Effectiveness of renal denervation in the treatment of hypertension: a literature review - Riya Tejas Shah; Brian Xiangzhi Wang (BMC, 2022)
Abstract Background Catheter-based renal denervation has been studied as a potential therapeutic option to reduce high blood pressure (BP). Preclinical studies in some experimental models have demonstrated an antihypertensive effect of renal denervation but reports from clinical trials have been mixed Methods We performed a literature search using combinations of the key terms 'Cardiovascular diseases, Clinical trial, Pre-clinical trials, Resistant hypertension, Renal denervation, Ablation technique, Radiofrequency ablation, Ultrasound ablation, RADIANCE SOLO, SYMPLICITY HTN, SYPRAL HTN'. The databases searched were PubMed and OVID Medline. Results The initial SYMPLICITY HTN-1 AND HTN-2 clinical trials reported significant decreases in office BP but results from the more robustly designed SYMPLICITY HTN-3 trial, which included sham controls and ambulatory BP monitoring, showed no significant antihypertensive effect. Interest in the use of renal denervation in hypertension was once again sparked by favourable results from the SPYRAL HTN-OFF Med trial Conclusion We provide a thorough, critical analysis of key preclinical and clinical studies investigating the efficacy of catheter-based renal denervation as a treatment for hypertension and highlight future areas for research to allow better translation into clinical practice